A characterization of the Logarithmic Least Squares Method - Csató, László (European journal of operational research, 2019)
•Derivation of preference vectors from pairwise comparison matrices is addressed.•We provide an axiomatic characterization of the Logarithmic Least Squares Method.•It is the only reasonable weight vector invariant to a transformation of triads.•The use of any other methods requires explaining the violation of this axiom. We provide an axiomatic characterization of the Logarithmic Least Squares Method (sometimes called row geometric mean), used for deriving a preference vector from a pairwise comparison matrix. This procedure is shown to be the only one satisfying two properties, correctness in the consistent case, which requires the reproduction of the inducing vector for any consistent matrix, and invariance to a specific transformation on a triad, that is, the weight vector is not influenced by an arbitrary multiplication of matrix elements along a 3-cycle by a positive scalar.